TORC1 signaling modulates Cdk8-dependent GAL gene expression in Saccharomyces cerevisiae. Issue 4 (5th October 2021) - Horvath, Riley; Hawe, Nicole; Lam, Cindy; Mestnikov, Konstantin; Eji-Lasisi, Mariam; Rohde, John; Sadowski, Ivan
Abstract: Cdk8 of the RNA polymerase II mediator kinase complex regulates gene expression by phosphorylating sequence-specific transcription factors. This function is conserved amongst eukaryotes, but the signals and mechanisms regulating Cdk8 activity and phosphorylation of its substrates are unknown. Full induction of the GAL genes in yeast requires phosphorylation of the transcriptional activator Gal4 by Cdk8. We used a screen to identify regulators of the Cdk8-dependent phosphorylation on Gal4, from which we identified multiple mutants with defects in TORC1 signaling. One mutant, designated gal four throttle 1 ( gft1 ) was identified as a recessive allele of hom3, encoding aspartokinase, and mutations in hom3 caused effects typical of inhibition of TORC1, including rapamycin sensitivity and enhanced nuclear localization of the TORC1-responsive transcription factor Gat1. Mutations in hom3 also inhibit phosphorylation of Gal4 in vivo at the Cdk8-dependent site on Gal4, as did mutations of tor1, but these mutations did not affect activity of Cdk8 assayed in vitro . Disruption of cdc55, encoding a regulatory subunit of the TORC1-regulated protein phosphatase PP2A, suppressed the effect of hom3 and tor1 mutations on GAL expression, and also restored phosphorylation of Gal4 at the Cdk8-dependent site in vivo . These observations demonstrate that TORC1 signaling regulates GAL induction through the activity of PP2A/Cdc55 and suggest that Cdk8-dependent phosphorylation of Gal4 is opposed by PP2A/Cdc55 dephosphorylation. These results provide insight into how induction of transcription by a specific inducer can be modulated by global nutritional signals through regulation of Cdk8-dependent phosphorylation. Abstract : Horvath, Hawe et al . examine regulators of Cdk8-dependent Gal4 activity in a screen for defects in the LTA response of gal3 yeast. They identify TORC1 components tor1 and tco89 and the downstream PP2A/Cdc55 phosphatase as regulators of Gal4. Additionally, genetic analysis indicates that mutations in hom3, which encodes aspartate kinase, produce defects in TOR signaling. These results demonstrate that regulation of Gal4 by phosphorylation is modulated by the TOR nutritional signaling pathway through the activity of PP2A/Cdc55.